Effects of Vitamin E and Vitamin C on Mercury Induced Toxicity in Mice (Progressive Agriculture, 2013)
The present study was undertaken to find out the efficacy of vitamin E and/or vitamin C against mercury (Hg) induced toxicity in mice. Sixty mice were randomly divided into 5 equal groups (n=12). One group of mice (Group A) was kept as control and each of rest four groups (B, C, D and E) were fed with mercuric chloride (HgCl2) in drinking water @ 65 mg/L. In addition to HgCl2 alpha-tocopherol (vitamin E) @ 100 mg/L, ascorbic acid (vitamin C) @ 250 mg/L and combination of vitamin E and vitamin C at same dose were given to the mice of groups C, D and E respectively. All treatments were continued for 28 consecutive days. Four mice of each group were sacrificed on day 1, 14 and 28 and efficacy of vitamin E and vitamin C against Hg induced toxicity were evaluated by observing toxic signs, body weight, hemato-biochemical parameters and postmortem lesions. Mild (++) toxic signs as evident by reduced feed and water intake, salivation, vomiting, excitement, muscle tremor, ataxia, restlessness, incordination and ruffled hair coat were observed from 2nd week (group B) and from 3rd week (group C and D) by intoxication with HgCl2. Significant (P